2021
DOI: 10.1021/acs.jpclett.1c01362
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Ligand and Cation Exchange of Colloidal CdSe Nanoplatelets toward PbSe Nanoplatelets for Application in Photodetectors

Abstract: Cation exchange emerged as a versatile tool to obtain a variety of nanocrystals not yet available via a direct synthesis. Reduced reaction times and moderate temperatures make the method compatible with anisotropic nanoplatelets (NPLs). However, the subtle thermodynamic and kinetic factors governing the exchange require careful control over the reaction parameters to prevent unwanted restructuring. Here, we capitalize on the research success of CdSe NPLs by transforming them into PbSe NPLs suitable for optoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Classified as solution-processed semiconductor nanocrystals with size- and shape-dependent luminescence emission, colloidal quantum dots (QDs) cover a spectral range from ultraviolet to near-infrared due to the quantum confinement effect. , To date, extensive attention has been paid to research on how to synthesize high-quality QDs with a near-unity photoluminescence quantum yield (PLQY) and color-pure emission, demonstrating their potential for applications in a variety of optoelectronic devices such as lasers, light-emitting diodes, , photodetectors, , liquid-crystal displays, and single-photon sources . Although stable luminescence emission plays an essential role in their widespread applications in these fields, most synthesized QDs are prone to blinking at the single-particle level, , which is especially significant at high excitation intensities.…”
mentioning
confidence: 99%
“…Classified as solution-processed semiconductor nanocrystals with size- and shape-dependent luminescence emission, colloidal quantum dots (QDs) cover a spectral range from ultraviolet to near-infrared due to the quantum confinement effect. , To date, extensive attention has been paid to research on how to synthesize high-quality QDs with a near-unity photoluminescence quantum yield (PLQY) and color-pure emission, demonstrating their potential for applications in a variety of optoelectronic devices such as lasers, light-emitting diodes, , photodetectors, , liquid-crystal displays, and single-photon sources . Although stable luminescence emission plays an essential role in their widespread applications in these fields, most synthesized QDs are prone to blinking at the single-particle level, , which is especially significant at high excitation intensities.…”
mentioning
confidence: 99%
“…Semiconductor nanocrystals are typically synthesized with ligands containing long alkyl chains, such as oleate and n -octylamine, which impede inter-nanocrystal electronic coupling and carrier transport in nanocrystal solids . Consequently, effort has been committed to replacing these native ligands with smaller, inorganic ligands. These studies have included halometallate ligands of general formula MX n z– , with CdCl 3 – and PbI 3 – as some specific examples. Kovalenko and co-workers demonstrated that halometallate ligation of semiconductor nanocrystals stabilized their dispersions in polar solvents and retained high nanocrystal photoluminescence efficiencies . Talapin and co-workers reported that CdCl 3 – ligands afforded high-concentration CdTe nanocrystal inks and also functioned as grain-growth promoters in sintered films, which were employed in high-efficiency solar cells .…”
mentioning
confidence: 99%
“…A partial Cd 2+ -to-Pb 2+ cation exchange applied to CdSe tetrapods yielded heterostructured PbSe-tipped CdSe tetrapods with PL maxima tunable from 1000 nm to more than 2000 nm . A facile procedure recently developed by Galle et al combines ligand and cation exchanges on CdSe NPLs (Figure a) . In this process, oleate-capped CdSe NPLs simultaneously undergo a ligand exchange to NH 4 I and a cation exchange reaction to PbSe in a two-phase mixture of hexane/MFA under mild conditions, preserving their morphology and crystal structure.…”
mentioning
confidence: 99%
“…Tracing of the frequency-dependence and determination of the cutoff frequency of the device using a blue LED and a signal generator to modulate the light (f). Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
mentioning
confidence: 99%
See 1 more Smart Citation